Agricultural commercialization and smallholder farmers' food security in Nigeria - Ajisafe Oluwaseun Gabriel; Idiaye Chuks Onyeka; Oluwatayo Isaac Busayo (Western Balkan Journal of Agricultural Economics and Rural Development)
The study examined the impact of agricultural commercialization on the food security status of smallholder farmers in Nigeria, a nation where agriculture has a crucial role in both economic sustainability and food provision. Utilizing the most recent data from the Nigeria General Household Surveys (NGHS 2018/19) and employing an Instrumental Variable Probit regression model, the research assesses the relationship between the level of commercialization, as measured by the Household Commercialization Index (HCI), and food security outcomes among smallholder farmers. The outputs reveal a significant positive link between higher levels of commercialization and improved food security. Specifically, an increase in the HCI correlates with a notable rise in the probability of achieving food security, with a statistically significant average marginal effect (AME) of 0.061, highlighting the potential benefits of market-oriented farming practices. This study also considers various socio-economic factors, including household size, marital status, and access to credit, to understand their influence on food security. The obtained results underscore the significance of supporting agricultural commercialization as a strategy to enhance food security among smallholder farmers in Nigeria. Paper calls for targeted policy interventions to facilitate access to markets, improve agricultural education, and provide financial services to farmers, aiming to bolster commercial activities and, consequently, food security.